Three essays on financialization and (de)regulation - Şengül, Serkan (My University, 2020)
The purpose of this thesis is to investigate the financialization and regulations in three different views. The first essay examines the effects of regulations on the risk during the 2008 financial crisis. In order to cope with the effects of the crisis, the United States, Europe and other major economies, which constitute the basis of international financial architecture, have started to take measures rapidly. Priority has been given to eliminating the effects of the crisis on financial markets, and measures have been taken to create a new and strong financial architecture and restore financial stability. The second essay focused on measuring the systemic risks in Turkey’s banking sector by using two major measures of systemic risk that have been proposed in the literature: conditional value at risk (CoVaR) and marginal expected shortfall (MES). In order to compute the contribution of banking sector to systemic risks, the MES and ΔCoVaR measures are estimated for the six Turkish banks which are listed on the Borsa Istanbul (BIST) during 2000–2016 period by using Engle’s dynamic conditional correlation model. Both systemic risk measures (MES and ΔCoVaR) are analyzed to determine the relationships between some variables associated with bank characteristics (e.g., VaR (value at risk), size and leverage ratio) and banks' systemic risk contributions, via simple panel data regression methods. The third essay examines the relationship between financialization and investment decisions of non-financial corporations and the implications of these changes in their investment behaviour by using firm-level econometric data for Turkish manufacturing firms. The sample is composed of an unbalanced panel that is conducted with 107 and 56 publicly traded Turkish manufacturing firms for different time periods. The Arellano-Bond methodology is used in order to show whether there is any financialization indicator in Turkish manufacturing industry.

Bu tezin amacı finansallaşmayı ve regülasyonları üç farklı bakış açısıyla incelemektir. İlk makale, regülasyonların 2008 finansal krizi sırasında risk üzerindeki etkilerini incelemektedir. ABD, Avrupa ve uluslararası finansal mimarinin temelini oluşturan diğer büyük ekonomiler, krizin etkileriyle baş edebilmek için, hızla önlem almaya başladı. Öncelik, krizin finansal piyasalar üzerindeki etkilerini gidermeye verilmiş, yeni ve güçlü bir finansal mimarinin oluşturulması ve finansal istikrarın yeniden kazanılması için önlemler alınmıştır. İkinci makale, koşullu risk değeri (CoVaR) ve marjinal beklenen kayıp (MES) gibi literatürde önerilen iki ana sistemik risk ölçüsünü kullanarak, Türkiye bankacılık sektöründeki sistemik riskleri ölçmeye odaklanmaktadır. Sistemik risklere bankacılık sektörünün katkısını hesaplamak için, 2000–2016 döneminde Borsa İstanbul'da (BIST) listelenen altı Türk bankasının MES ve ΔCoVaR ölçüleri, Engle’in dinamik koşullu korelasyon modeli ile analiz edilmektedir. Banka özellikleriyle ilişkili bazı değişkenler (örneğin VaR-risk değeri-, boyut ve kaldıraç oranı vb. gibi) ile bankaların sistemik riske katkıları arasındaki ilişkinin tespit edilmesi için, her iki sistemik risk ölçümü (MES ve CoVaR), basit panel veri regresyon yöntemleri yoluyla analiz edilmektedir. Üçüncü makale, finansal olmayan şirketlerin yatırım kararları ve finansallaşma arasındaki ilişkiyi ve bu değişikliklerin yatırım davranışlarındaki etkilerini, Türk imalat firmaları için firma düzeyinde ekonometrik verileri kullanarak incelemektedir. Örneklem, 107 ve 56 adet halka açık Türk imalatçı firma için farklı zaman dilimlerini içeren düzensiz bir panelden oluşmaktadır. Türk imalat sanayinde herhangi bir finansallaşma göstergesinin olup olmadığını ortaya koymak için Arellano-Bond metodolojisi kullanılmaktadır.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2020
Keywords: Finansallaşma; Finansal kriz; Sistemik risk; Regülasyonlar; Financialization; Financial crisis; Systemic risk; Regulations